1990
DOI: 10.1002/ijc.2910460116
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a dtpa chelate conjugate for monoclonal antibody targeting to a human colonic tumor in nude mice

Abstract: Our previous studies with a 90Y-labelled antibody against carcinoembryonic antigen (CEA) conjugated to the cyclic anhydride-DTPA (CA-DTPA) indicated that the accretion of 90Y in the bone may limit the application of 90Y-labelled antibodies for therapy. In this report, we have compared the tumor targeting of CA-DTPA-conjugated antibody to antibody conjugated with 4 isothiocyanatobenzyl (ITC-Bz) derivatives of DTPA in nude mice bearing a human colonic tumor xenograft. In biodistribution studies using an 111In-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The pharmacokinetics and biodistribution of radiolabeled hLL1 or IMMU-110 were evaluated in naive (tumor-free) BALB/c mice. The benzyl-DTPA conjugate of hLL1 was prepared using 2-(4-isothiocyanatobenzyl)DTPA as described previously for similar humanized antibodies (15). Matrix-assisted laser desorption/ionization time-of-flight analysis of the benzyl-DTPA-hLL1 conjugate indicated an average of 0.98 benzyl-DTPA per unit of hLL1.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetics and biodistribution of radiolabeled hLL1 or IMMU-110 were evaluated in naive (tumor-free) BALB/c mice. The benzyl-DTPA conjugate of hLL1 was prepared using 2-(4-isothiocyanatobenzyl)DTPA as described previously for similar humanized antibodies (15). Matrix-assisted laser desorption/ionization time-of-flight analysis of the benzyl-DTPA-hLL1 conjugate indicated an average of 0.98 benzyl-DTPA per unit of hLL1.…”
Section: Methodsmentioning
confidence: 99%
“…O ur data in rats w ith infection con cur w ith previous studies in tumour-bearing athymic mice in which four different inIn-chelate-antibody com plexes showed similar tumour uptake but a very differ ent distribution in organs [4], Other studies have indicated that the most striking differences between radiometal-DTPA-antibody complexes and more stable chelates occur after the first 48 h post-injection [11,12]. The second aim of the study was to evaluate the pos sible advantage of using a protein larger than IgG for the detection of infection.…”
Section: Discussionmentioning
confidence: 65%
“…Naked hLL1 or 2L-Rap-hLL1-␥4P was conjugated to diethylenetriaminepentaacetic acid (DTPA) using 2-(4-isothiocyanatobezyl)DTPA (Macrocyclics, Dallas, TX), as described by Sharkey et al, 32 to obtain DTPA-hLL1 or DTPA-2L-Rap-hLL1-␥4P, which was labeled with 88 Y chloride (Los Alamos National Laboratory, Los Alamos, NM) or 111 In chloride (Perkin Elmer), respectively, for pharmacokinetic studies. Naive female SCID mice (8 weeks old, 18 to 22 g) were injected intravenously with a mixture of 0.001 mCi (0.037 MBq) 88 Y-DTPAhLL1 and 0.02 mCi (0.74 MBq) 111 In-DTPA-2L-Rap-hLL1-␥4P, supplemented with unlabeled DTPA conjugates of hLL1 or 2L-Rap-hLL1-␥4P, so that each animal received a total dose of 10 g each of hLL1 and 2L-Rap-hLL1-␥4P.…”
Section: Pharmacokinetics and Biodistributionmentioning
confidence: 99%